2004
DOI: 10.1002/art.20179
|View full text |Cite
|
Sign up to set email alerts
|

Validation and clinical significance of the Childhood Myositis Assessment Scale for assessment of muscle function in the juvenile idiopathic inflammatory myopathies

Abstract: Objective. To examine the measurement characteristics of the Childhood Myositis Assessment Scale (CMAS) in children with juvenile idiopathic inflammatory myopathy (juvenile IIM), and to obtain preliminary data on the clinical significance of CMAS scores.Methods. One hundred eight children with juvenile IIM were evaluated on 2 occasions, 7-9 months apart, using various measures of physical function, strength, and disease activity. Interrater reliability, construct validity, and responsiveness of the CMAS were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
126
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 186 publications
(133 citation statements)
references
References 15 publications
(24 reference statements)
0
126
0
7
Order By: Relevance
“…We have previously demonstrated that global skin disease activity correlates moderately with measures of physical function in children with juvenile DM (4,5). In adults with DM, Hundley et al have demonstrated that active skin disease is associated with reduced quality of life (6).…”
Section: Introductionmentioning
confidence: 91%
“…We have previously demonstrated that global skin disease activity correlates moderately with measures of physical function in children with juvenile DM (4,5). In adults with DM, Hundley et al have demonstrated that active skin disease is associated with reduced quality of life (6).…”
Section: Introductionmentioning
confidence: 91%
“…Physician and parent global assessments of disease activity and damage, using both Likert and VAS scales, were obtained (2,5). The Physician Global Disease Activity and Damage VAS score is an accepted standardized scoring system for assessing disease activity and damage (2,5).…”
Section: Patientsmentioning
confidence: 99%
“…Physician and parent global assessments of disease activity and damage, using both Likert and VAS scales, were obtained (2,5). The Physician Global Disease Activity and Damage VAS score is an accepted standardized scoring system for assessing disease activity and damage (2,5). Twenty-two patients (at one center) Ͼ4 years of age underwent manual muscle testing, which was performed by a pediatric physical therapist; this could not be performed in younger patients, as previously explained by Rider (6).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formal measures such as the Childhood Myositis Assessment Scale (CMAS) 6 and manual muscle testing of 8 groups (MMT8) 7 exist to standardize the muscle assessment. Both are part of the agreed Juvenile Dermatomyositis Paediatric Rheumatology International Trials Organisation 8 and International Myositis Assessment and Clinical Studies Group 9 core disease activity measures.…”
Section: Introductionmentioning
confidence: 99%